(untitled) (Investigación y Desarrollo, 2019)
This study focuses on an action research project related to the use of classical music to improve reading comprehension in a foreign language classroom at a university level in the town of Ambato, Tungurahua, Ecuador. The need for university students to improve reading skills in this society was analysed, due to the fact that young people have not developed reading habits, even in their mother tongue. This aspect was conside- red, as well as students’ results on reading exercises applied to them, before and after being exposed to the use of classical music in the language classroom, which were evaluated through a comparison between the different experiences revealed in the surveys applied to the students, and their grade reports. The conclusion highlights that there was a significant improvement in the academic performance of students when they felt comfortable in their classroom environment while classical music was played. Even though research has not yet proved scientifically that the use of classical music influences students to improve their reading comprehension in the language classroom, there are studies related to the use of classical music in education and the learning process, related to the topic of this study, which contributed to conclude that further research must be done in this specific area.